24-CHROMIUM FERRITIC STEEL MAGNETIC PROPERTIES - Nurdin Effendi; Tri Darwinto; Agus Hadi Ismoyo; Parikin Parikin (Jurnal Sains Materi Indonesia, 2014)
24-CHROMIUM FERRITIC STEEL MAGNETIC PROPERTIES. A 24-chromium ferritic stainless steel had been made by foundry methods. The purpose of this investigation is to investigate the magnetic behavior of this ferritic sample, as one of the divvy of its characteristics. Some of supporting data used to prove that the material sample was ferritic type and followed by hysteresis curve obtained from the experiment. By Vibrating Sample Magnetometer (VSM) equipment, it is found that the ferritic steel has the saturation induction around of 150 emu g-1, with the coercive force Hc is close to 3 x 10-4 T and the remanent induction Br is close to 1,1 x 10-3 emu g-1 meanwhile by permagraph equipment the saturation induction around of 3.13 kG, and the coercive force HcB is equal to 0.005 kOe and the remanent induction Br is 0.23 kG with the dissipasion energy BHmax zero, explains that the ferritic stainless steel has a relative good magnetic behavior with relative high magnetization at the relative weak external magnetic field and can be demagnetized easily, appropriate to soft magnetic materials.